TEACHER CAREER DEVELOPMENT LAW IN THE NEW NORMAL ERA A CASE STUDY OF PUBLIC TEACHER DEVELOPMENT IN INDONESIA - Muh Bukhari; Saiful Wathan (Scientium Law Review (SLR), 2022)
The spreading of the Covid-19 pandemic to many countries in the world since December 2019, including Indonesia, has made teaching and learning policies happen online. This creates many challenges, including the career development of teachers, especially in public schools. This must be handled considering that the positions filled with potential are based on the leadership's subjectivity, and government agencies' performance must be objective and based on results with measurable quantity and quality. Based on the normative juridical study, two conclusions were drawn. First, developing a teaching career during the Covid-19 pandemic requires individual abilities and emotional maturity of above-average levels to make quick, accurate, and accountable decisions. Second, to produce maximum organizational performance, the government must regulate the concept of teacher career development whose quantity and quality are measurable, such as an analysis of strengths, weaknesses, opportunities, and threats (SWOT) and the Quantitative Strategic Planning Matrix (QSPM).